The Analysis Study of Association of Dyslipidemia and Diabetic Retinopathy: A Comprehensive Systematic Review - Anindi Putri Harjanti; Yuliani (International Medical Journal Corp. Ltd, 2024)
Introduction: Diabetic retinopathy (DR) is a leading cause of blindness in diabetic patients, and its progression is influenced by various factors, including dyslipidemia. This systematic review aims to assess the relationship between dyslipidemia and DR, focusing on lipid profiles such as LDL cholesterol, HDL cholesterol, triglycerides, and total cholesterol. Method: We conducted a systematic review of studies published between 2010 and 2023 that examined the association between dyslipidemia and DR in diabetic patients. Studies were selected based on inclusion criteria, including cross-sectional, cohort, and case-control designs. Data regarding lipid profiles, DR stages, and statistical significance were extracted and analyzed. Result: The literature search was conducted across reputable databases such as Science Direct, PubMed, and SagePub. After a rigorous three-level screening process, eight relevant studies were selected for detailed evaluation. These studies varied in design, including cross-sectional, cohort, and retrospective studies, and involved diverse sample sizes ranging from 45 to over 79 million participants. The findings consistently indicated a significant association between dyslipidemia and diabetic retinopathy (DR). Several studies reported elevated levels of low-density lipoprotein (LDL) and triglycerides (TGs) and reduced levels of high-density lipoprotein (HDL) in patients with DR compared to those without. Additionally, certain studies suggested a protective effect of statins on non-proliferative diabetic retinopathy (NPDR), while medications such as pitavastatin and fenofibrate were associated with a reduced prevalence of proliferative diabetic retinopathy (PDR) and vitreous hemorrhage. Discussion: The findings suggest that dyslipidemia, particularly elevated LDL and reduced HDL cholesterol levels, contributes to the development and progression of DR. However, the lack of clear temporal precedence and the absence of control groups in some studies limit the ability to establish causality. The heterogeneity in study designs also affects the generalizability of the results. Conclusion: Dyslipidemia plays a significant role in the development and progression of diabetic retinopathy. Future research should focus on high-quality longitudinal studies that account for confounders and temporal relationships to better understand the causal link between dyslipidemia and DR.